Effect of surfactants on swelling capacity and kinetics of alginate-chitosan/CNTs hydrogel. (24th May 2019) - Bibi, Azeem; Sadiq-ur, Rehman; Faiz, Rashida; Akhtar, Tasleem; Nawaz, Mohsan; Bibi, Saira
Abstract: Nanocomposite hydrogels of alginate-chitosan matrix with nanofillers, functionalized multi-walled carbon nanotubes (COOH-MWCNTs) were first time synthesized in cationic, anionic, mixture of cationic and anionic surfactants and in the absence of surfactants by employing solution casting method. Whole process of synthesis was carried out under greener source of heating i.e., ultrasonic waves. Synthesized films were evaluated by Fourier transform infrared spectroscopy and scanning electron microscopy which reveal uniform dispersion of nanofillers in matrix. Synthesized hydrogels were also newly explored for swelling capacity. Swelling ratio of hydrogels was measured in distilled water, saline solutions and in solutions of different pH. Swelling pattern of prepared films indicates that these materials are very stable and can show best performance in different pH and kinds of solutions. Effect of concentration ratio of nanofillers to matrix and nature of surfactants on swelling ability was also appraised and indicated that trace amount of nanofillers gives fascinating results. Process of swelling and deswelling of synthesized films was taken place by super case-II transport mechanism, which is effected by amount of nanofillers and nature of surfactant.